THE EFFECT OF CORPORATE GOVERNANCE MECHANISM, LEVERAGE, AND PROFITABILITY ON FINANCIAL DISTRESS WITH LIQUIDITY AS MODERATING VARIABLES IN MANUFACTURE COMPANIES LISTED ON INDONESIA STOCK EXCHANGE (IDX) - Nurhujaima, Nurhujaima (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study aims to determine the effect of corporate governance mechanisms, leverage and profitability in manufacturing sector companies on the Indonesia Stock Exchange. In addition, this study also aims to determine whether liquidity can be used as a moderating variable in the model. The research design is a causal relationship research with a quantitative approach. The sample in this study were 48 manufacturing companies listed on the Stock Exchange in 2009 to 2018. The type of data used in this study is secondary data. Data analysis techniques used multiple linear regression analysis and interaction testing (moderating) which was done with the help of Eviews 9 software. The results in this study indicate that the mechanism of corporate governance, leverage and profitability affect financial distress simultaneously and partially. Liquidity is a moderating variable for the relationship between leverage and financial distress. However, liquidity is not a moderating variable for the relationship between corporate governance mechanisms and profitability for financial distress in manufacturing sector companies listed on the Indonesia Stock Exchange.